A new framework for the unity of Muslims: some reflections - Mumtaz Ali, Mohammad; Mughal, Muhammad Junaid (Institute of Social Sciences & Development, Pakistan, 2019)
The phenomenon of the presence of Muslims all over the world by naturalization and migration is being understood in terms of a new concept, “Transnational Islam” for the united Muslim Ummah. The sense of the unity of Muslim Ummah has been always integral to Muslim conscience throughout the ages. Transnational Islam, it is expected, being a modern rubric, will create, on one side, the sense of oneness of Ummah in the presence of so many nationalities and, on the other, loyalty to individual countries. It would be helpful to face multi-dimensional challenges posed by the modern world for Muslims and humanity. To face and overcome the impending challenges, the Muslims need to study their current phenomena afresh but in the light of the teachings and spirit of the Qur’an and Sunnah. They also need to come up with a realistic and practical framework. This proposal, therefore, identifies obstacles and suggests as solution, the regeneration of the revivalist intellectual tradition of Islam and its framework.